KEANEKARAGAMAN JENIS RAYAP DI KEBUN KELAPA SAWIT PT. BUMI PRATAMA KHATULISTIWA KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Habibi, .; Diba, Farah; Siahaan, Sarma (Universitas Tanjungpura, 2017)
Subterranean termites has found as a pest in oil palm plantation. The research aimed to identification the subterranean termites which attack in oilpalm plantation of PT Bumi Pratama Khatulistiwa. The site place was in oilpalm plantation in Sungai Ambawang Subdistrict, Kubu Raya Regency. Field collection of termites was conducted in three block which high severe by termites attack. Result of the research showed that three termites species was found. The first species was Coptotermes sp, found in all three blocks. The second species was Schedorhinotermes sp found in two block of site reseacrh. The last species was Microtermes sp. All the termites was catagorize as subterranean termites. The termites found in oilpalm tree and in dead wood around the oilpalm tree. It is necessary to conduct the regular monitoring to prevent termites attack in oilpalm plantation. Keywords: Coptotermes sp, Microtermes sp, oilpalm plantation, Schedorhinotermes sp, termites